DOMESTICATION OF FRESHWATER PUFFER FISH OR BUNTAL (Tetraodon palembangensis) - I Wayan Subamia; Nina Meilisza; Sudarto Sudarto; Slamet Sugito (Indonesian Aquaculture Journal, 2008)
The Research Institute for Freshwater Ornamental Fish Culture has been conducting domestication research since 2004 on adult freshwater puffer fish or buntal broodstock in which the fish were reared in aquaria and fed with small feed fish teri (anchovy) and earthworm (Lumbricus sp.). The domestication of freshwater puffer fish or buntal has resulted in successful environmental adaptation and reproductive ability of the fish and further rearing of its fry. The adaptive ability was indicated by its high survival rate, good growth and development, and the reproductive success in spawning, egg production, hatching as well as growing of the larvae to fry stages. The mature gonad stage of the fish was reached at an average body weight of 150 g with a reproductive period of 5 months. The spawning occurred naturally and the eggs were gradually released at interval periods of 14—18 days with egg production rates of 1,000—1,900 eggs per spawning. The highest egg fertilization rate was 96%, with the highest egg hatching rate of 78.6%. Hatching process took place on the 6th to 13th days after spawning process. The surviving larvae began feeding filtered natural foods Moina sp. on the 3rd day up to the 6th day, whereas unfiltered Moina sp. was given from the 7th to 14th days. The fish were fed the live feed Culex sp. from the 15th to 30th days. In the following period the fish was fed earthworm and small feed fish teri (anchovy).